Simulation study on opinion formation models of heterogeneous agents based on game theory and complex networks. (November 2017) - Li, Ying; Cao, Hongduo; Wen, Genfeng
This study investigates a new opinion formation model of heterogeneous agents, a network stubborn individuals and orators (NSO) model based on game theory and complex social networks. Game theory solves economists' rational choice-making problems, and complex social networks reflect the social impact on opinion evolution. The NSO model involves both social and individual heterogeneous characteristics. In a society, the more unequal the members, and the closer the social distances, the faster opinions spread. In the real world, the power-law degree distribution and the short paths in social networks can generate the rapid spread of an opinion. This study also investigates opinion control under the NSO model. The results show that opinion guidance is most likely to separate the public into different groups rather than converge to the guide's opinion.